EVALUATION OF THE EFFECT OF SOLID WASTE BURNING AT MOULAY ISMAIL HOSPITAL OF MEKNES CITY ON THE SOIL - Nour-Eddine, Ameziane; Taoufik, Hassouni; Lahcen, Benaabidate; Abdelkader, Chahlaoui (European Scientific Journal, ESJ, 2014)
The management of the hospital waste constitutes one of the main challenges with which our societies are confronted; but unfortunately, only few researches has been conducted with regards to the management of hospital waste. Most establishments of health especially in the private sector throw their waste in the garbage dumps, which can provoke the contamination of grounds and ground-water sheets. Thus, the sanitary establishments which make the treatment of their waste are rare. A more practiced treatment is the incineration process, of which the consequences are very fatal on the environment if it is made without appropriate filtering: discharge of smokes which is a toxic waste, if not polluting the atmosphere (US EPA: USA–.Environment Protection Agency, 2006). This work is realized on the ground of the Moulay Ismail hospital in Meknes. Before 2006, the waste of this hospital was always treated in open-air burned. This practice which does not correspond to the international standards leads to the formation of the dioxins which are toxic matter, and are harmful to the human health and to the environment. These substances constitute a group including 210 chlorinated tricyclic organic compounds which include dioxins (PCDDs [Polychlorinated dibenzodioxins] / PCDFs [Polychlorinated dibenzofurans]). Thus, we took analyses of the ground of Moulay Ismail hospital in Meknes to look for these substances. In this work, we made use of chromatography in gaseous phase connected to the mass spectrometry (GC/MS); it is the method of choice to identify and quantify PCDD / Fs to the state of tracks in the complex matrices (Eppe et al., 2006). Therefore, the dosage demonstrated the absence of any organic polluting substances.